Pregnancy Stress and Childhood Stunting: The Mediating Role of Maternal Mental Health in Primary Healthcare - Ahmad Mumtaz Tauba; Yusfina Modesta Rua; Elfrida Dana (Inspirasi Foundation, 2027)
Introduction: Stunting remains a major public health challenge in Indonesia, particularly in rural and border areas such as East Nusa Tenggara. Emerging evidence suggests that maternal psychological factors, including pregnancy stress and mental health disorders, play a critical role in child growth outcomes. However, the mediating role of maternal mental health in the relationship between antenatal stress and stunting remains underexplored in primary healthcare settings. Objective: To analyze the relationship between pregnancy stress and stunting incidence through maternal mental health as a mediating variable at Puskesmas Umanen, Atambua. Method: This study employed an analytical observational design with a cross-sectional approach conducted in March 2026. A total of 210 respondents (pregnant women and mothers with children aged 0–24 months) were selected using purposive sampling. Data were collected using validated instruments: Perceived Stress Scale (PSS), Edinburgh Postnatal Depression Scale (EPDS), and anthropometric measurements (height-for-age Z-score). Data were analyzed using mediation analysis with regression models (PROCESS Macro), with significance set at p < 0.05. Results: Pregnancy stress was significantly associated with stunting incidence (p < 0.05). Maternal mental health (depression/anxiety) significantly mediated this relationship (indirect effect p < 0.01), indicating a partial mediation model. Higher levels of stress increased the risk of poor maternal mental health, which in turn significantly increased the likelihood of stunting. Conclusion: Maternal mental health plays a significant mediating role in the relationship between pregnancy stress and stunting. Integrating mental health screening into antenatal care services is essential to reduce stunting risk in primary healthcare settings.